Example Non Example Learning Model to Improve 21st Century Skills in Students - Naily Fatkhiyati (Proceeding International Conference on Religion, Science and Education, 2023)
21st century skills are skills that must be mastered by everyone in order to respond to the complex challenges of life in the 21st century. The 21st century learning process is carried out by increasing High Order Thinking Skills (HOTS). Higher order thinking skills is the idea of Bloom’s Taxonomy which aims to foster basic skills for students which are summarized in the 4Cs: Critical Thinking, Collaborative, Creativity, and Communicative. Example non example is a learning model that uses images as a medium to present subject matter. The example non example learning model is expected to be able to support students to have 21st century skills. Applying Higher Order Thinking Skills by training students’ thinking skills through pictures or videos displayed by the teacher. By practicing higher order thinking skills will foster 21st century skills including critical thinking that can be applied when students begin to analyze the images that have been displayed by the teacher. Through groups formed by teachers, students are able to apply collaboratively, students work together to solve problems given by the teacher. Students are able to apply communicative skills by communicating their ideas with their group friends. In this case, students work together, exchange opinions and express ideas through the results of the discussion, from here comes creativity by students.